2015
DOI: 10.3945/jn.114.199778
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grain Oats Improve Insulin Sensitivity and Plasma Cholesterol Profile and Modify Gut Microbiota Composition in C57BL/6J Mice

Abstract: In mice, WGOs improved insulin sensitivity and plasma cholesterol profile compared with LBOs, and the effects were associated with the changes in cecal microbiota composition. Increasing WGO consumption may help improve insulin sensitivity and dyslipidemia in chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 63 publications
4
36
1
1
Order By: Relevance
“…The administration of 3 g/day of ␤-glucans to 33 polypectomized patients showed no effects on the fecal cultivable lactobacilli and bifidobacteria (27). An increased level of lactobacilli was found in animal models after a barley-or oat-containing diet, especially using high-viscosity ␤-glucans (22,23,24). At the same time, an oat product-based diet or ␤-glucans from Laminaria digitata, Laminaria hyperborea, and Saccharomyces cerevisiae did not increase the levels of lactobacilli in pigs and rats (25,50).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The administration of 3 g/day of ␤-glucans to 33 polypectomized patients showed no effects on the fecal cultivable lactobacilli and bifidobacteria (27). An increased level of lactobacilli was found in animal models after a barley-or oat-containing diet, especially using high-viscosity ␤-glucans (22,23,24). At the same time, an oat product-based diet or ␤-glucans from Laminaria digitata, Laminaria hyperborea, and Saccharomyces cerevisiae did not increase the levels of lactobacilli in pigs and rats (25,50).…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, oat ␤-glucans did not favor the growth of Clostridium sp. in SHIME and C57BL/6J mouse models (21,24,49). However, several discrepancies between the different studies might be due to the different models and methods used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, correlations between gut microbiota and grains have also been identified in other studies. Zhou et al [45] fed mice with whole grain oat or low bran oat flour for eight weeks and found that the two experimental groups had different compositions of intestinal microbiota. Carvalho-Wells et al [46] found that maize-derived whole grain was correlated with an increased level of bifidobacteria in the human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Whole grain feeding impacted energy intake that was associated with changes in metabolomics profile of gut microbiome derived metabolites and gut hormone changes [104]. Zhou et al clearly described that feeding of whole grains dominantly changes gut microbiome and improve insulin sensitivity and other metabolic measures in mice models [105]. Whole-grain barley feeding known to decrease the high fat diet-induced inflammation that is possibly related to formation of short chain fatty acids i.e.…”
Section: Introductionmentioning
confidence: 99%